PENGARUH METODE EXAMPLE NON EXAMPLE TERHADAP KOMPETENSI IPA PESERTA DIDIK PADA MATERI INTERAKSI MAKHLUK HIDUP - Lufri Lufri; Amrianto Amrianto; Azwir Anhar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
Preliminarily, it was found that there are some problems faced by teachers in teaching and learning process. The problems are the teachers still implement classical rather than cooperative learning. Moreover, it is hard for them to make students active in the classroom, especially in asking questions and delivering ideas or opinions. Furthermore, it is also hard for them to develop students' curiosity in learning process. To overcome these problems, one solution which can be used is implementation of example non example method. The purpose of the research was to know the effect of example non example method on students' competence. It was a quasi experimental research. It was done in SMPN 18 Padang to VII grade students. Purposive sampling technique was used to take samples. The data were obteined through observation sheets for psychomotor competence. The technique of data analysis used Mann-Whitney U-Test in assistance of SPSS software. The findings show that the example non example method has significant effect on students' psychomotor competence.